A FTIR Study of the Acidity of in situ Generated Brønsted Sites on NaY via Displacement Reactions. Issue 14 (26th June 2019) - Wu, Jingcheng; Murphy, Brian M.; Gould, Nicholas S.; Wang, Chenguang; Ma, Longlong; Xu, Bingjun
Abstract: Extrinsic Brønsted acid sites (BAS) on zeolites are generated on NaY upon exposure to organic acids through an ion exchange process. However, the acid‐base chemistry of species adsorbed on the zeolites is largely unexplored. In this work, organic acids with varying acidity are employed to investigate the proton‐transfer displacement within the micropores of NaY. The direction and degree of the displacement reactions are monitored by in situ transmission Fourier transform infrared (FTIR) spectroscopy. Two organic acids are sequentially introduced to NaY, and the direction and extent of the displacement reaction are followed by the diagnostic vibrational band of the adsorbed carboxylate species, i. e., ν([O−C−O] − ). Stronger acids are able to displace dissociatively adsorbed weaker acids on NaY, which is analogous to the solution‐phase acid‐base chemistry favoring the formation of weaker acids by stronger acids. The gas phase deprotonation energy correlates more closely with displacement reaction than pKa, which is explicitly defined in the aqueous solution of acids. A thermochemical cycle is constructed to rationalize the observation that acid‐base reactions in the zeolite pores could be predicted with the gas phase acidity of compounds involved in the displacement reactions. Abstract : Acids in zeolites : Organic acids with varying acidities are employed to investigate the proton‐transfer displacement within the micropores of zeolite NaY. Stronger acids are able to displace dissociatively adsorbed weaker acids, which is analogous to the solution‐phase acid‐base chemistry favoring the formation of weaker acids by stronger acids. A Born‐Haber cycle is constructed to rationalize the close correlation between ▵Hdis of the reaction and ▵GPDE of the acid pair.